AN ESTIMATION OF FREQUENCY AND SPECTRUM OF CHROMOSOMAL ABERRATIONS IN PATIENTS WITH CONNECTIVE TISSUE DYSPLASIA IN CONDITIONS OF BLOOD CELLS CONTACT WITH NANOSTRUCTURED MATERIALS - М. V. Dvornichenko (Бюллетень сибирской медицины)
In order to evaluate cytogenetic effect of nanocomposite materials used in traumatology and orthopedics an investigation of chromosomal aberration ins in the culture of lymphocytes short-term contacted with artificial material (nanostructured titanium samples of implants bearing bilateral calcium phosphate coating) in patients with dysplasia of connective tissue (DCT) and osteogenesis imperfecta (OI) has been conducted. A reduction of percent of aberrant cells having single or/and paired chromosomal breaks as compared with spontaneous mutagenesis (without model samples) was revealed under introduced biocompatible composites into blood cell cultures of patients with DCT or OI. Analysis of frequency and spectrum of chromosomal aberrations in blood cells can be considered as potential prognostic criterion and a predictor of implant’s efficacy in the surgical treatment of DCT and OI complications.